Theory and design of terabit optical fiber transmission systems - Bottacchi, Stefano
"This comprehensive, modular treatment of the challenging issues involved in very high-speed optical transmission systems contains all the theory and practical design criteria required to optimize transmission system design"--
Machine generated contents note: 1. Optical modulations and spectra; 2. Principles of nonlinear optics and light polarization; 3. Light amplification and noise in optical amplifiers; 4. Noise analysis and BER theory of optical fiber transmission systems; 5. Theory and applications of the Mach-Zehnder interferometer; 6. Interferometric optical responses; 7. Basic optical modulations and direct detection systems; 8. High-order optical modulation formats; 9. Theory of coherent optical detection; 10. Architecture and design of Terabit transmission systems.
Includes bibliographical references and index.
Keywords: Optical fiber communication